Pembentukan Spiritualitas Mahasiswa Pendidikan Agama Kristen sebagai Calon Guru PAK di STT Katharos Indonesia Bekasi - Daniel Halomoan Marbun; Martinus Laia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The diversity of students’ study motivations in theological higher education presents both challenges and opportunities in shaping the spirituality of prospective Christian Religious Education (CRE) teachers. Not all students enter the CRE program based on a calling to ministry, resulting in varying levels of initial spiritual readiness. This study aims to analyze the process of spiritual formation among CRE students as prospective teachers at STT Katharos Indonesia Bekasi in the context of diverse study motivations, referring to James W. Fowler’s theory of faith development. This research employs a qualitative descriptive approach using observation, in-depth interviews, and documentation involving CRE students. The findings reveal that despite diverse initial motivations, the integrated theological education process through academic learning, ministry practices, community life, and spiritual formation effectively fosters faith growth and personal encounters with Christ. This process contributes to the development of students’ spiritual maturity. The study concludes that CRE education functions as an effective means of faith transformation in preparing prospective teachers with strong spiritual integrity and readiness for ministry.